2019
DOI: 10.1101/841601
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Targeted complement inhibition at synapses prevents microglial synaptic engulfment and synapse loss in demyelinating disease

Abstract: Multiple sclerosis (MS) is a demyelinating, autoimmune disease of the central nervous system. While work has focused on axon loss in MS, far less is known about synaptic changes. Here, in striking similarity to other neurodegenerative diseases, we identify in postmortem human MS tissue and in nonhuman primate and mouse MS models profound synapse loss and microglial synaptic engulfment. These events can occur independently of local demyelination, neuronal degeneration, and peripheral immune cell infiltration, b… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
104
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(107 citation statements)
references
References 86 publications
(146 reference statements)
3
104
0
Order By: Relevance
“…5j). Similar to what happens in the thalamus of MS patients 31 , we found a significant increase in synaptic phago-cytosis specifically in MS1 cortical microglia ( Fig. 5j-k), which is in line with an overall increased phagocytic capacity of MS1 microglia as indicated by increased CD68 expression ( Fig.…”
Section: Ms1 and Ms2 Subgroups Differentially Associate With Corticalsupporting
confidence: 86%
See 1 more Smart Citation
“…5j). Similar to what happens in the thalamus of MS patients 31 , we found a significant increase in synaptic phago-cytosis specifically in MS1 cortical microglia ( Fig. 5j-k), which is in line with an overall increased phagocytic capacity of MS1 microglia as indicated by increased CD68 expression ( Fig.…”
Section: Ms1 and Ms2 Subgroups Differentially Associate With Corticalsupporting
confidence: 86%
“…Surprisingly, we did not detect an overall decrease in pre-synaptic density in SPMS cortex, despite evidence for increased synapse phagocytosis by microglia. Although loss of synapses has been extensively reported in hippocampus 39,40 , thalamus 31 and spinal cord of MS patients 41 , evidence for a loss of synapses in the cortex is more ambiguous. Reduced spine density on apical dendrites, indicating post-synaptic loss, has been shown in both myelinated and demyelinated cortex of MS patients 9 , whereas other studies, using similar methods to ours, only found a significant loss of synaptophysin in leukocortical demyelinated lesions but not in normal appearing MS cortex 42 and no correlation with cortical atrophy 43 .…”
Section: Discussionmentioning
confidence: 99%
“…This raises the question of whether Csmd1 could affect which ages, regions, neurons, and synapses are more or less vulnerable to complement-dependent processes. As a recent paper found that inducing retinal ganglion cells to exogenously express Crry, a known complement inhibitor, protects not only the retinogeniculate synapses from complement deposition and microglial engulfment, but also neighboring synapses (though to a lesser degree) (Werneburg et al, 2020), non-cell autonomous effects could add another layer of complexity. Much of our mechanistic study focused on glutamatergic cells and synapses, and we found Csmd1 to be preferentially co-localized with glutamatergic synaptic markers in early postnatal mouse cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of RGMa in spinal cord injury results in a block to regrowth of motor neurons, but treatment with anti-RGMa antibody could overcome this inhibition (Hata et al, 2006). Synaptic loss is thought to play a role in declining cognitive function in Alzheimer's disease (Hong et al, 2016;Werneburg et al, 2020), and anti-RGMa had an effect on neural growth and connectivity in multiple sclerosis and spinal cord injury (Demicheva et al, 2015;Hata et al, 2006). Intracellular signaling elicited by neurotrophins is mediated in part by protein prenylation (Li et al, 2013), suggesting a link between neurotrophins and RGMa which has been shown to act through a prenylation pathway (Siebold et al, 2017).…”
Section: Discussionmentioning
confidence: 99%